2015
DOI: 10.1039/c4lc01416b
|View full text |Cite
|
Sign up to set email alerts
|

Regenerating the cell resistance of micromolded PEG hydrogels

Abstract: Polydimethylsiloxane stamp materials used during soft lithography undermine the non-fouling behaviour of bio-inert PEG-based hydrogels, resulting in increased protein adsorption and cell adhesion and migration on the gel. This previously unreported phenomenon undermines the function of lab-on-a-chip devices that require the device to be bio-inert, and slows the implementation of promising micromolding and imprinting methods for 3D culture and commercial cell culture systems. We illustrate that the degree of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…By extension, this conclusion stipulates that poly(ethylene glycol) (PEG)-based hydrogels are bio-inert [42] and do not present integrin binding sites and are prone to cause M1 macrophage polarization. Further studies with other bio-inert polymers can elucidate whether this conclusion can be generalized.…”
Section: Resultsmentioning
confidence: 99%
“…By extension, this conclusion stipulates that poly(ethylene glycol) (PEG)-based hydrogels are bio-inert [42] and do not present integrin binding sites and are prone to cause M1 macrophage polarization. Further studies with other bio-inert polymers can elucidate whether this conclusion can be generalized.…”
Section: Resultsmentioning
confidence: 99%
“…S5). Increasing A-PEG density on the surface resulted in decreasing cell attachment since PEG is known to resist cell attachment [55][56][57]. Cell density is known to regulate MSC osteogenic differentiation through the competitive influences of cell spreading (via cytoskeletal tension) and intercellular contact [58].…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, with at least six EG units, the OEGterminated lms derived from the C 10 EG n series on Si (111) surfaces and prepared at low vacuum conditions ($1 mbar) effectively resisted the protein adsorption, which was comparable to those lms derived from OEG-terminated thiolates on Au (111) surfaces that also displayed increasing protein resistance with longer EG chain length. 49,53,57,78 C 10 EG n lms on Si(111) prepared at medium vacuum conditions…”
Section: Resultsmentioning
confidence: 99%
“…7,10 Although excellent proteinresistant properties have been demonstrated for zwitterions [34][35][36] and polypeptides 37 coatings, ultrathin lms presenting OEG are still among the most widely used and the most protein-resistant coatings studied to date. [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] Moreover, we recently demonstrated that the high resistance to non-specic protein adsorption of OEG lms allows the selective attachment of proteins onto the nanopatterns generated on such lms by local oxidation using conductive atomic force microscopy (AFM). 58,59 We and others have reported the photo-activated graing of the a-OEG-u-alkenes onto hydrogen-terminated silicon, forming OEG-terminated monolayers that are directly bound to the silicon substrate via Si-C bonds (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation